IMPROVING SENSORY AND QUALITY PROPERTIES OF YOGURTS FROM GOAT’S MILK - А. А. Shunekeyeva; M. K. Alimardanova; A. A. Majorov; G. S. Yeszhanov; O. V. Koltyugina (Academic Scientific Journal of Chemistry, 2021)
Fermented milks, which are highly-consumed foods in the world and more nutritious compared to milk, have high contents of proteins, minerals and vitamins. In general, the overall properties of yogurt, such as acidity level, the production of aroma compounds as well as the sensory profile (appearance, color and texture), are important traits which have a decisive role in consumer acceptance of products. Goat milk yogurts were manufactured with the supplementation of 5% cherries, 5% blackthorn fruits, and 5% mixture of two. Yogurts were characterized based on compositional, microbiological and safety properties of the added fruit pulp and sensory analyses during storage (15 d at 5°C). Compared with control samples yogurt made by using fruits and berries had higher protein content and sensory properties, but also higher acidity values. Goat milk yogurts without additions, in particular, had better physical characteristics. Using supplements caused the changing structure of yogurt, leading to higher syneresis values. Yogurt with mixed of two fillers was the best accepted among the yogurts. For the parameters used, a mix of cherries and blackthorn has promising features as suitable ingredients for goat milk yogurt manufacture. The overall acceptability decreases when adding the non-roasted amaranth flour in a product. The main weakness of this study was the paucity of size of our panel (10 people). With a small sample size, caution must be applied, as the findings might not be transferable to show objective data